$C_λ$-semiconservative $FK$-spaces - Dagadur, I. (Ukrains’kyi Matematychnyi Zhurnal, 2012)
We study $C_λ$-semiconservative $FK$-spaces for $C_λ$-methods defined by deleting a set of rows from the Cesaro matrix $C_1$ and give some characterizations.